Rancang Bangun Aplikasi Manajemen Barbershop untuk Optimasi Booking dan Laporan Keuangan - Roys Pakaya (Program Vokasi Universitas Negeri Gorontalo, 2026)
The management of barbershop businesses that still relies on conventional methods creates various challenges, particularly in customer booking records, transaction management, and financial reporting. The use of conventional recording media may result in poorly organized data, vulnerability to loss or damage, and difficulties in information retrieval and processing. In addition, unstructured financial management can hinder business owners' ability to monitor cash flow, thereby affecting the effectiveness of business decision-making.To address the challenges of digitalization, this study designed and developed a web-based Barbershop Management Application as an integrated solution that combines customer data management, service booking scheduling, payment transaction recording, and automated financial reporting within a centralized platform. The system architecture was developed using the Waterfall method through the stages of requirements analysis, system design, implementation, functional system evaluation, and maintenance. The application was developed as a web-based system to ensure accessibility across various internet-connected devices.The testing results showed that Black Box Testing achieved a 100% success rate, while the User Acceptance Test (UAT) obtained a user acceptance score of 89%, indicating that the application is easy to use and that its functionality meets user needs. Therefore, the application is considered feasible for implementation to support more modern, structured, and efficient barbershop management.